Cold shock combined with salicylic acid treatment alleviated postharvest chilling injury of wax apple by maintaining cell membrane and cell wall integrity - Liangyi Zhao; Xiangying Che; Ziling Qi; Yonghua Zheng; Peng Jin (Postharvest Biology and Technology, 2027)

High-temperature resistant homogeneous imidazolium functionalized poly (phthalazinone ether sulfone) anion exchange membranes for electrodialysis - Fanchen Sun; Qian Liu; Lin Zhuo; Xuefu Che; Peng Shi; Weiwei Kong; Yiping He; Hongyuan Lu; Lan Gong; Shouhai Zhang; Xigao Jian (Desalination, 2026)

Agricultural management intensity drives niche partitioning of ammonia oxidizers at three contrasting soil sites - Yu Zeng; Che Tan; Chang Yin; Xiaozhong Wang; Hongsheng Gao; Hua Peng; Yongchao Liang (Applied Soil Ecology, 2026)

Meteorological regime controls on PM2.5 and O3 variability in the Sichuan Basin: insights from a hybrid causal-machine learning analysis - Yuyi Du; Xin Qi; Miao Feng; Hanxiong Che; Fumo Yang; Xin Long; Dasheng Huang; Shumin Zhang; Chao Peng; Yang Chen (Atmospheric Environment, 2026)

A physics-informed neural network for continuous rice canopy thermal monitoring and forecasting from sparse UAV observations - Peng Xie; Yuan Wang; Changwen Du; Jing Che; Haitao Xiang (Computers and Electronics in Agriculture, 2026)

Geometrically consistent ordinal mixture-of-experts for weight estimation of sows from multi-view point clouds - Qiang Zhai; Longhu Ma; Han Jiang; Li Wan; Yunhan Liu; Yiran Liao; Yifeng Yang; Changmeng Peng; Jinglan Lei; Yong Zhuo; Lianqiang Che; De Wu (Computers and Electronics in Agriculture, 2026)

Sulfated dialogues: How brown algae polysaccharides orchestrate gut-host crosstalk through structure-encoded signals - Jing Xu; Yanjing Liu; Sitong Che; Mengqian Ma; Wanyu Tang; Peng Zhang; Yuanqiang Guo (Trends in Food Science & Technology, 2026)

A distinct electrochemical mechanism governing chalcopyrite flotation in hematite-rich IOCG ores - Wei Che; Richard Lee; Yongjun Peng (Minerals Engineering, 2026)

Functional probiotic Ligilactobacillus agilis Z22 enhances gut–lung immune defense in chickens through TLR2/IL-10–JAK1/STAT3 signaling - Qiao Guo; Yingjie Wang; Jiahui Wu; Zhenghao Che; Shan Lv; Wenqing Zhao; Shiying Li; Jin Liu; Xiuli Peng (Food Bioscience, 2026)

Robust ultralong multicolor phosphorescence with high-temperature resistance and dynamic stimulus-responsive color-changing afterglow enabled by in situ synergetic rigidification - Wenjing Chen; Jiqiu Yang; Yi Zhu; Pengfei Du; Shujuan Liu; Jinxiu Che; Yinna Zhang; Jing Yang; Baozhong Lü; Feng Peng; Zhengjun Shi (Chemical Engineering Journal, 2026)

Retraction notice to “Cable-car measurements of vertical aerosol profiles impacted by mountain-valley breezes in Lushan Mountain, East China” [Sci. Total Environ. 768 (2021) 144198] - Jing Duan; Yong Chen; Wenling Wang; Jun Li; Xiaopeng Zhang; Guangxian Lu; Yunfei Che; Shujun Zhong; Shupo Ma; Peng Li; Junling An; Pingqing Fu (Science of The Total Environment, 2026)

A gradient boosting-based machine learning framework for improving atmospheric visibility numerical prediction - Chen Han; Hong Wang; Ke Gui; Xutao Zhang; Wenjie Zhang; Yue Peng; Yang Zhao; Zhaodong Liu; Huizheng Che; Xiaoye Zhang (Atmospheric Research, 2026)

The CMA Chemistry–Weather Coupled Model and Its Operational Forecast of Fog–Haze and Sand/Dust Storms - Hong Wang; Xiaoye Zhang; Wenjie Zhang; Yue Peng; Ping Wang; Hongli Liu; Zhaorong Zhuang; Liping Huang; Weihong Tian; Yang Zhao; Ke Gui; Chen Han; et al. (Journal of Meteorological Research, 2026)

Port integrated energy system planning with multi-energy collaboration under uncertainty - Zongwei Che; Qian Zhang; Zhen Cao; Yun Peng; Zhong Chu; Wenyuan Wang (Ocean Engineering, 2026)

Research progress on the characteristics of milk allergens and the effect of Maillard reaction and its assistance treatment on allergenicity - Xiaowen Pi; Tanying Zhang; Jia Cao; Zeyu Peng; Bowen Li; Haozhe Yi; Wanxiang Guo; Jing Che; Chen Wang; Jinshen Chu (Food Chemistry, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Data-driven optimization of a composite ducted propeller based on a bi-directional FSI method - Xiaoyi An; Chengshan Li; Peng Wang; Huachao Dong; Che Liu; Youjiang Wang (Ocean Engineering, 2026)

Polystyrene microplastics disrupt the blood-testis barrier via CEBPB-driven lysosomal autophagy and induce ferroptosis-like injury in human sperm, compromising embryo development - Man Wu; Lei Li; Tianxin Zhao; Yuling Mao; Jiajing Lin; Xiaomin Li; Yanling Bai; Feixue Han; Shuyan Chen; Tianwen Peng; Chen Liao; Xin Ye; et al. (Journal of Hazardous Materials, 2026)

Can existing land-use intensification mitigate urban heat and reduce carbon emissions in megacities? evidence from Shanghai - Peng Zeng; Yaoyi Liu; Lili Dong; Yao Wang; Yue Che (Journal of Cleaner Production, 2026)

Contrasting landscape distribution of soil particulate versus mineral-associated organic carbon in a subtropical forest - Runxia Zhang; Bingwei Zhang; Danying Peng; Shuilin Che; Chencheng Zhang; Chengjin Chu (Geoderma Regional, 2026)

Exploring the multiple photochemical behaviors of ionizable EDCs in aquatic environments: Kinetics, intermediates, and toxicity evolution - Linke Ge; Shijing Yang; Nannan Cui; Chang-Er Chen; Xiaojia Che; Peng Zhang (Environmental Research, 2026)

Formation mechanisms of foraminifera-dominated silt–sand sheets in the Baiyun Sag, South China Sea: The role of Kuroshio and North Pacific Intermediate Water - Chengkun Deng; Xiaojie Wei; Zhiqian Gao; Tailiang Fan; Zhongtao Zhang; Ronald J. Steel; Leyi Xu; Hairong Wang; Haojie Gao; Tiangui Che; Lingxue Peng (Marine Geology, 2026)

Enrichment mechanism and clean utilization of sodium-iron in high alkali and high iron coal in Beishan coal Mine, Xinjiang - Jiaxin Li; Hongyang Bai; Wenfeng Wang; Hengyan Liu; Kexin Che; Peng Wang; Qingfeng Lu (Fuel, 2026)

Volatile odor characterization of electrohydrodynamically (EHD) dried garlic products based on HS-GC-IMS and HS-SPME-GC-MS - Peng Guan; Wei Zuo; Zhiqing Song; Chuanqiang Che; Hao Chen; Yun Jia; Chunxu Qin; Jingli Lu; Changjiang Ding (Food Research International, 2026)

Data-Driven assessment of demand response potential of residential loads based on LSTM-WGCNA and Customer directrix load - Bo Peng; Baolin Cui; Xin Ma; Che Liu (Energy and Buildings, 2026)

Structure–reactivity relationships in UV/chlorine degradation, NDMA formation, and cytotoxicity of chlorpheniramine and doxylamine - Shih-Wen Peng; Pei-Jin Lin; Ya-Hong Lin; Che-Hsin Lee; Yu-Chun Tseng; Ming-Cyuan He; Wei-Hsiang Chen (Journal of Hazardous Materials, 2026)

Quantifying the influencing factors on the spatiotemporal patterns of dune activity in the Tengger Desert, Northwestern China - Xuehua Che; Zhuolun Li; Shipei Dong; Jie Luo; Yingyibing Shen; Xue Peng (Geomorphology, 2026)

Ball-milling pretreatment-driven low-temperature waste cotton fibers-based hard carbon anodes for sodium-ion batteries - Yingying Zhou; Tiantao Huang; Zixin Lv; Che Wang; Junjun Peng; Aiping Jin; Jun Xiong; Linghui Yu; Ming Li; Zhongchen Ma; Jinchao Wei; Qing Chen (Biomass and Bioenergy, 2026)

Effects of high-pH saline-alkaline water on tissue structure, osmoregulation, antioxidant capacity, and metabolic activity in mud crab Scylla paramamosain Estampador, 1950 - Yuntao Li; Cunhong Chen; Zihui Li; Jingli Yang; Chenxi Che; Shan Gao; Kangxiang Qin; Peng Yang; Ziwei Fan; Wenjun Li; Chunlin Wang; Changkao Mu; et al. (Aquaculture, 2026)

Green infrastructure for urban cooling and carbon neutrality: Building-integrated strategies from heat mitigation to public health - Wanqiao Che; Chenwei Peng; Weimin Zhuang (Urban Forestry & Urban Greening, 2026)

Mechanisms of cavitation erosion risk enhancement by vortex generators at lower Reynolds numbers - Ning Qiu; Haitao Rao; Doubin Xun; Han Zhu; Baowei Shan; Bangxiang Che; Peng Wu (Ocean Engineering, 2026)

AI-driven framework for high-precision seamless sunshine duration estimation using Himawari-8 satellite and ground observations - Honglei Wu; Zhaohua Liu; Zhaoliang Zeng; Ke Gui; Zhijian Lin; Peng Xie; Ruqing Zhu; Zhehao Liang; Yaqiang Wang; Huizheng Che (Atmospheric Research, 2026)

Study on characteristic aroma compounds of Qingke baijiu and their biosynthesis mechanism - Lihua Chen; Qinghua Peng; Yuhang Chen; Fuhong Che; Zhanxiu Chen; Shengbao Feng (Food Research International, 2025)

Biomimetic adhesive-free self-splicing enables scalable wood film for programmable hygromorphic soft actuators - Wenbo Che; Yufeng Miao; Yifan Liu; Runxuan Wang; John Moyo; Youming Yu; Wenhui Bao; Yunyan Peng (Chemical Engineering Journal, 2025)

Transport Patterns of Seasonal Suspended Particulate Matter Around the Western Sunda Shelf - Hui Zhang; Shengfa Liu; Kaikai Wu; Lina Ai; Peng Cao; Yazhi Bai; Xiaojing Wang; Hongmin Wang; Che Abd Rahim Mohamed; Somkiat Khokiattiwong; Narumol Kornkanitnan; Xuefa Shi (Journal of Ocean University of China, 2025)

Geochemical Compositions and Transport Patterns of Surface Sediments from the Malacca Strait - Lina Ai; Shengfa Liu; Hui Zhang; Peng Cao; Xue Li; Wenjing Qi; Kaikai Wu; Che Abd Rahim Mohamed; Xuefa Shi (Journal of Ocean University of China, 2025)

Climate teleconnections among the Earth’s three poles - Anmin Duan; Xin Li; Wenting Hu; Tao Che; Jun Hu; Yuzhuo Peng; Chao Zhang; Die Hu; Yuheng Tang; Zhulei Pan; Qilu Wang; Guoxiong Wu (Science Bulletin, 2025)

Corrigendum to ‘Chronic Cr(VI) exposure-induced biotoxicity involved in liver microbiota-gut axis disruption in Phoxinus lagowskii Dybowski based on multi-omics technologies’ [Environ. Pollut., 368 (2025) 125759] - Xinchi Shang; Xinghua Che; Kai Ma; Wenxue Guo; Shanshan Wang; Zhi Peng Sun; Wei Xu; Yongquan Zhang (Environmental Pollution, 2025)

Metastructure for broadband vibration suppression and ultra-low frequency energy harvesting by integrating intercell negative stiffness mechanism with 2-DOF oscillators - Zilong An; Che Xu; Chun H. Wang; Shuhua Peng; Yaowen Yang; Junlei Wang; Liya Zhao (Engineering Structures, 2025)

Long-term variations in aerosol optical properties in Beijing: insights from diurnal and nocturnal continuous measurements - Shiya Peng; Yu Zheng; Lei Li; Ke Gui; Jibiao Zhu; Shuhui Liu; Haoling Zhang; Hujia Zhao; Huizheng Che; Xiaoye Zhang (Atmospheric Environment, 2025)

Role of lanthanum oxycarbonate in dendritic fibrous Ni/CHE-La catalyst on enhanced CO2 dissociation for low-temperature CO2 reforming of methane - Shi Yan Liew; Aishah Abdul Jalil; Tan Ji Siang; Fazilah Farhana Abdul Aziz; Anees Ameera Fauzi; Nurfatehah Wahyuny Che Jusoh; Lee Peng Teh; Saravanan Rajendran (Journal of Environmental Chemical Engineering, 2025)

Complex networks reveal teleconnections across cascading floods in the Yangtze River Basin - Fengyun Sun; Alfonso Mejia; Sanjib Sharma; Peng Zeng; Yi’na Hu; Kai Yang; Yue Che (Natural Hazards, 2025)

Inhibition of PERK-eIF2α-ATF4 signaling enhances the antiviral effects of resveratrol-loaded nanoparticles against enterovirus 71 in hand, foot, and mouth disease - Bin Wang; Lihe Che; Peng Zhang; Luyao Sun; Yue Yu; Na Du (Archives of Virology, 2025)

Nonlinear dynamics and vibration mechanisms in air scroll compressors: A study on orbiting and fixed scroll pair - Xiao-Liang Yang; Bin Peng; Ming-Lang Che; Jian-Fei Shi; Zhi-Xiang Liao; Yu-Bo Zhang (International Journal of Refrigeration, 2025)

Involvement of the PINK1/Parkin signaling pathway in 4-vinylcyclohexene diepoxide-induced ovary toxicity in rats - Yue Che; Xiaozhu Wang; Qian Li; Xiyi Peng; Zhen Liu; Wenhui Xu; Mei Jiang; Ting Wang; Jian Gao; Weiling Wang (Food and Chemical Toxicology, 2025)

Intermediate water engineering in wood hydrogels for ultra-low enthalpy solar desalination - Shutong Zhang; Yunyan Peng; Xiaolong Xu; Jingqing Sun; Jiawei Lu; Yi Zhang; Wenbo Che; Youming Yu (Chemical Engineering Journal, 2025)

Investigation of water migration behavior in biopolymer- modified sand: A multiscale analysis - Wenyue Che; Jin Liu; Ke Ma; Tingwei Huang; Peng Wu; Jianbing Peng (Engineering Geology, 2025)

Effects of the southwest vortex on the vertical structure of ozone in the Sichuan Basin in China - Huiqiong Ning; Hong Wang; Ping Kang; Zhaodong Liu; Yue Peng; Wenjie Zhang; Chen Han; Yang Zhao; Wei Liu; Ping Wang; Huizheng Che (Atmospheric Pollution Research, 2025)

A lignin-wood Janus membrane with three-dimensional interconnected layered micro/nano channels for on-demand separation of surfactant-stabilized oil/water emulsions - Yifan Liu; Yufeng Miao; Zhuo Huang; Runxuan Wang; Yunyan Peng; Xiaolong Fang; Wenbo Che; Youming Yu (Desalination, 2025)

Deep Hypothermic Low Flow Results in Multiple Aspects of Neurological Deficits in Mice by eEF2 Hyperphosphorylation - Yumei Liao; Dongyang Che; Peng Liu; Xinyu Wang; Yanlin Zhang; Lingling Guo; Jinlin Hu; Tianyao Li; Mei Fong Lam; Nan Ma; Shiqing Zhang; Hua Lu; et al. (Molecular Neurobiology, 2025)

Impact of diurnal variation in 3D urban landscape metrics on land surface temperature in Shanghai: A local climate zone perspective - Hongchao Xu; Fengyun Sun; Peng Zeng; Xingyan Bao; Yue Che (Energy and Buildings, 2025)

Sources and light absorption of brown carbon in urban areas of the Sichuan Basin, China: Contribution from biomass burning and secondary formation - Chao Peng; Mi Tian; Guangming Shi; Shumin Zhang; Xin Long; Hanxiong Che; Jie Zhong; Xiangyu You; Zhier Bao; Fumo Yang; Xin Qi; Chongzhi Zhai; et al. (Atmospheric Research, 2025)

Developing hydrothermal stable SAPO-11 catalysts to convert glucose into 5-HMF - Yutong Che; Peng Lu; Jinlei Zhang; Xiaosheng Wang; Yukang Liu; Hailong Yu; Yuxiang Liu (Fuel, 2025)

Mitigating ACQ and enhancing solubility: A dual strategy for real-time aquatic product freshness detection - Siying Che; Anni Xu; Jiaxin Zou; Shuhua Luo; Xiutan Peng; Haiyan Fu; Yuanbin She (Food Research International, 2025)

Study on the contribution of the major desert groups on SDS weather in East Asia combining the model simulation and multiple observations - Huiqiong Ning; Hong Wang; Zhaodong Liu; Yue Peng; Wenjie Zhang; Chen Han; Yang Zhao; Ping Wang; Hailin Gui; Jikang Wang; Huizheng Che; Xiaoye Zhang (Atmospheric Research, 2025)

3,4-Dihydroxybenzoic acid methyl ester from Vespa velutina auraria Smith against rheumatoid arthritis via modulating the apoptosis and inflammation through NF-κB pathway - Yi-Hao Che; Chao-He Liu; Xiu-Qin Pang; Heng Liu; Zhi-Bin Yang; Jia-Peng Wang; Huai Xiao (Inflammopharmacology, 2025)

Risks of respiratory and circulatory system diseases induced by exposure to PM2.5 in high humidity and low solar radiation environments: disease types, genes, and functions - Xiaomeng Li; Liru Zhang; Zhengliang Zhang; Xuan Li; Jingli Qian; Jiawei Zhou; Hanxiong Che; Yan Han; Xin Qi; Fumo Yang; Yu Huang; Chao Peng; et al. (Environmental Geochemistry and Health, 2025)

Development and evaluation of an electrical impedance tomography (EIT) sensor for real-time monitoring of hemolysis dynamics - Piao Peng; Yue Fu; Bo Che; Xuan Li; Lei Liu; Jing Sun; Teng Luo; Linhong Deng (Analytica Chimica Acta, 2025)

Two episodes of lunar basaltic volcanism in Mare Fecunditatis as revealed by Luna-16 soil samples - Svetlana Demidova; Alexander Nemchin; Renaud Merle; Yue Guan; James Head; Katherine Helen Joy; Clive R. Neal; Martin Whitehouse; Mikhail Ivanov; Xiao-Lei Wang; Xiaochao Che; Cyril Lorenz; et al. (Geochimica et Cosmochimica Acta, 2025)

Corrigendum to “Effects of aquatic Ca2+ and Mg2+ on the antioxidant, immune, osmotic regulation, molting, and metabolic abilities of Scylla paramamosain” [Aquaculture, Volume 586, Part 2, 15 February 2025, 741875] - Yuntao Li; Chenxi Che; Shan Gao; Kangxiang Qin; Peng Yang; Ziwei Fan; Wenjun Li; Chunlin Wang; Changkao Mu; Huan Wang (Aquaculture, 2025)

Evolutionary history of the Malacca Strait driven by sea level changes over the last 16 ka - Lina Ai; Shengfa Liu; Hui Zhang; Peng Cao; Xiao Wu; Lianhua He; Wenjing Qi; Kaikai Wu; Che Abd Rahim Mohamed; Houjie Wang; Xuefa Shi (Global and Planetary Change, 2025)

Analysis of dominant microorganisms and core enzymes in Qingke Baijiu Daqu by high-throughput sequencing and proteomics - Lihua Chen; Qinghua Peng; Yuhang Chen; Fuhong Che; Zhanxiu Chen; Shengbao Feng (Food Research International, 2025)

Chronic Cr(VI) exposure-induced biotoxicity involved in liver microbiota-gut axis disruption in Phoxinus lagowskii Dybowski based on multi-omics technologies - Xinchi Shang; Xinghua Che; Kai Ma; Wenxue Guo; Shanshan Wang; Zhi Peng Sun; Wei Xu; Yongquan Zhang (Environmental Pollution, 2025)

The optimized nitrogen rate reduced ammonia emissions from rice paddies in the cold region of Northeast China - Shiting Bi; Pengfei Li; Jiarui Lv; Qiang Dong; Xiangyu Luo; Yeqi Che; Muhammad Rehman Naseer; Zhilei Liu; Cailian Yu; Xianlong Peng (European Journal of Agronomy, 2025)

Effects of aquatic Ca2+ and Mg2+ on the antioxidant, immune, osmotic regulation, molting, and metabolic abilities of Scylla paramamosain - Yuntao Li; Chenxi Che; Shan Gao; Kangxiang Qin; Peng Yang; Ziwei Fan; Wenjun Li; Chunlin Wang; Changkao Mu; Huan Wang (Aquaculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Mechanical deformation destabilizing hydrate within thermodynamic equilibrium region - Peng Zhang; Xueping Chen; Rui Bao; Xu Ma; Yulu Wang; Yangli Che; Lianhai Zhang; Yingmei Wang; Jing Zhan; Guangjun Guo; Changyu Sun; Jianyang Wu; et al. (Fuel, 2025)

Using Gaussian Mixture Model Clustering for the Automated Segmentation of Cerebral Arteriovenous Malformations in Magnetic Resonance Images - Ting-Yu Lin; Cheng‑Chia Lee; Yu-Wei Chen; Hsiu-Mei Wu; Ching-Jen Chen; Huai-Che Yang; Syu-Jyun Peng (Journal of Medical and Biological Engineering, 2025)

Applicability of Different Indices for Delineating the Boundary of Arid Region: A Case Study in Northwestern China - Xue Peng; Xiang Li; Yingyibing Shen; Xuehua Che; Shipei Dong; Zhuolun Li (Journal of Earth Science, 2025)

Assessing the interaction of oceanic and riverine processes on coastal phytoplankton dynamics in the East China Sea - Jiawei Gao; Rong Bi; Julian P. Sachs; Yaoyao Wang; Yang Ding; Hong Che; Jing Zhang; Peng Yao; Jie Shi; Meixun Zhao (Marine Life Science & Technology, 2025)
The interaction of riverine inputs and ocean current systems causes complex spatiotemporal variations in phytoplankton dynamics in marginal seas of the northwest Pacific Ocean, yet quantitative assessments of these variations and their causes remain limited. Here we evaluate phytoplankton biomass and community structure changes using lipid biomarkers, accompanying ocean circulation and nutrient variations in surface waters collected in spring and summer of 2017–2018 at 118 sites in the East China Sea off the Zhejiang coast. High biomass of diatoms, inferred from brassicasterol concentrations, shifted from the south in spring to the north in summer, while high dinoflagellate biomass, inferred from dinosterol concentrations, occurred mainly in the Changjiang (Yangtze) River plume and adjacent areas in both seasons. Seasonal variation in phytoplankton distribution was linked to the spatial extents of water masses such as the Changjiang Diluted Water (CDW) and the intrusion of the Kuroshio Subsurface Water (KSSW). A three end-member mixing model was applied to quantify water mass contributions. The results showed that an increase in the KSSW (from 0 to 40%) and a decrease in the CDW (from 100 to 20%) resulted in a significant (20%) increase in diatom proportions and a significant (20%) decrease in dinoflagellate proportions. Dinoflagellate proportions were highest in the CDW-dominated region, while diatoms and total phytoplankton biomass were higher in the CDW–KSSW mixing region and the KSSW-dominated region. This study highlights the dynamic response of the phytoplankton community to water mass changes in marginal seas that can aid coastal ecosystem management.

Effects of bicarbonate on antioxidant, immune, osmolytic and metabolic capabilities of Scylla paramamosain - Chenxi Che; Yuntao Li; Kangxiang Qin; Ziwei Fan; Wenjun Li; Shan Gao; Peng Yang; Chunlin Wang; Changkao Mu; Huan Wang (Aquaculture, 2025)

A comprehensive molecular phylogeny of the genus Sylvirana (Anura: Ranidae) highlights unrecognized diversity, revised classification and historical biogeography - Yun-He Wu; Man-Hao Xu; Chatmongkon Suwannapoom; Sang Ngoc Nguyen; Robert W. Murphy; Theodore J. Papenfuss; Amy Lathrop; Felista Kasyoka Kilunda; Wei Gao; Zhi-Yong Yuan; Jin-Min Chen; Liang Zhang; et al. (Molecular Phylogenetics and Evolution, 2025)

Black soldier fly and microbiome collaborate to bioconvert the tofu whey water in an efficient and environment-friendly manner - Xiaowen Ji; Shaojie Zhou; Wenwen Chen; Bin Cao; Yumeng Sun; Qiyang Che; Yinglao Zhang; Jibin Zhang; Ting Ding; Jiaping Xu; Feng Peng; Maoye Li; et al. (Journal of Water Process Engineering, 2025)

Metabolic transformation of paralytic shellfish toxins in the mussel Mytilus galloprovincialis under different exposure modes - Guanchao Zheng; Hanyu Che; Haiyan Wu; Yuxiang Deng; Mengmeng Guo; Jixing Peng; Qianqian Geng; Zhijun Tan (Harmful Algae, 2025)

Characteristics and health risks assessment of PM2.5-bound heavy metals during winter in urban areas of northern China: A case study in Kaifeng - Xin Qi; Yan Han; Hanxiong Che; Jiawei Zhou; Chao Peng; Zhier Bao; Yiliang Liu; Lingshuo Meng; Shumin Zhang; Fumo Yang; Wenbo Xue; Yu Lei; et al. (Science of The Total Environment, 2024)

Secondary Successional Forest Soil Bacterial Community Variation Correlates to Soil Type - Peng Jiang; Xin Wan; Mingxuan Che; Jingping Chen; Mingxue Liu (Water, Air, & Soil Pollution, 2024)

Establishment and Validation of Sandell-Kolthoff Method for Saliva Iodine Determination - Yue Su; Ming Li; Honglei Xie; Xin Hou; Meng Zhao; Jia Li; Haowen Pan; Zexu Zhang; Zongyu Yue; Wenjing Che; Lanchun Liu; Jiasen Cao; et al. (Biological Trace Element Research, 2024)

Allergenicity risk in animal-based food proteins: Source, dietary factors effect, allergen detection and processing modification methods - Yanxiang Bi; Changqi Liu; Fei Pan; Wenjun Peng; Xiaoming Fang; Huilian Che; Wenli Tian (Trends in Food Science & Technology, 2024)

Population exposure disparities between residential and working areas during a cold wave event in Changchun, China - Hongchao Xu; Peng Zeng; Fengyun Sun; Hongyu Zhao; Yue Che (Applied Geography, 2024)

Non-ecological factors affect human interaction with urban nature and perception of cultural ecosystem services - Tian Tian; Sitong Huang; Yifan Wu; Peng Zeng; Yaoyi Liu; Yue Che (Sustainable Cities and Society, 2024)

Long-term addition of organic manure stimulates the growth and activity of comammox in a subtropical Inceptisol - Yu Zeng; Che Tan; Lei Zhang; Lelin You; Wanning Zheng; Hao Chen; Hongyun Peng; Chunyan Wu; Yongchao Liang (Science of The Total Environment, 2024)

Micafungin protects mouse heart against doxorubicin-induced oxidative injury via suppressing MALT1-dependent k48-linked ubiquitination of Nrf2 - Li-Qun Lu; Ming-Rui Li; Lin-Lu Huang; Yan-Xi Che; Ya-Nan Qi; Xiu-Ju Luo; Jun Peng (Chemico-Biological Interactions, 2024)

The relationship between resistance evolution and carbon metabolism in Staphylococcus xylosus under ceftiofur sodium stress - Qianwei Qu; Haixin Peng; Mo Chen; Xin Liu; Ruixiang Che; God’spower Bello-Onaghise; Zhiyun Zhang; Xueying Chen; Yanhua Li (Archives of Microbiology, 2024)

Geographic inequalities in park visits to mitigate thermal discomfort: A novel approach based on thermal differences and cellular population data - Peng Zeng; Yaoyi Liu; Tian Tian; Yue Che; Marco Helbich (Urban Forestry & Urban Greening, 2024)

An ion synergism fluorescence probe via Cu2+ triggered competition interaction to detect glyphosate - Siying Che; Yiwan Zhuge; Xiutan Peng; Xingxing Fan; Yao Fan; Xiahe Chen; Haiyan Fu; Yuanbin She (Food Chemistry, 2024)

Identification of synthetic cathinone positional isomers using electron activated dissociation mass spectrometry - Peng Che; Christina Chang; Patrick Buzzini; Lavinia Stegemann; Jeroen Kool; J. Tyler Davidson; Isabelle Kohler (Analytica Chimica Acta, 2024)

A fluorescence ionic probe utilizing Cu2+ assisted competition for detecting glyphosate abused in green tea - Siying Che; Yiwan Zhuge; Xinxiang Shao; Xiutan Peng; Haiyan Fu; Yuanbin She (Food Chemistry, 2024)

Corrigendum to “p-Phenylenediamine induces immediate contact allergy and non-histaminergic itch via MRGPRX2” [Chem. Biol. Interact. 351 (2022):109751] - Delu Che; Jiapan Gao; Xueshan Du; Yi Zheng; Yajing Hou; Bin Peng; Tao Jia; Songmei Geng; Langchong He (Chemico-Biological Interactions, 2024)

Deciphering the functional importance of comammox vs. canonical ammonia oxidisers in nitrification and N2O emissions in acidic agricultural soils - Che Tan; Chang Yin; Lei Zhang; Yu Zeng; Cécile Gubry-Rangin; Hao Chen; Zixiang Gao; Hongyun Peng; Tingqiang Li; Yongchao Liang (Soil Biology and Biochemistry, 2024)

Developing Ni/SAPO-11 deoxygenation catalysts using yttrium modified SAPO-11 prepared by rice husk ash - Zitong Li; Peng Lu; Caina Song; Yutong Che; Xiaosheng Wang; Zhiwei Lyu; Yuxiang Liu (Fuel, 2024)

Report on the 4th Board Meeting of the International Human Phenome Consortium - Mei Tian; Han Liu; Shiwen Peng; Zhong Yang; Weishuo Tao; Huiting Che; Xuanxuan Gao; Li Jin (Phenomics, 2024)

Vertical distributions of lipid biomarkers in spring and summer in coastal regions of the East China Sea - Jiawei Gao; Shulan Xu; Rong Bi; Yaoyao Wang; Yang Ding; Hong Che; Jing Zhang; Peng Yao; Jie Shi; Meixun Zhao (Frontiers in Marine Science, 2024)
Lipid biomarkers are amongst the most widely used proxies in studies of the structure and functioning of marine food webs. However, vertical distributions of lipid biomarkers and their controlling mechanisms remain unclear, especially in highly dynamic coastal ecosystems. Here we tested vertical profiles of key lipid biomarkers (sterols and fatty acids) in suspended particles and their correlations with water masses in spring of 2017 and summer of 2018 in the Zhejiang coasts of the East China Sea. The Changjiang Diluted Water, the Taiwan Strait Water and the Kuroshio Subsurface Water showed strong contributions in the surface layer in spring, the surface layer in summer, and the deep layer in both seasons, respectively. Accordingly, lipid biomarker composition also varied between different water layers. Overall, lipid biomarker concentrations in the surface layer were around 2 ~ 7 times higher than those in the deep layer, indicating high phytoplankton biomass in the surface layer. The ratio of docosahexaenoic acid to eicosapentaenoic acid was also higher in the surface layer, especially in the south of our study region, suggesting high nutritional quality of particulate organic matters in the surface layer. Significant correlations between the depth profiles of lipid biomarkers and water masses suggested the control of water masses on lipid biomarker production. The distribution patterns of lipid biomarkers in our study are consistent with previous findings on zooplankton grazing and fish larvae, highlighting the significance of lipid biomarkers as trophic markers to study food web structure and functioning in highly dynamic coasts.

Key characteristics of new particle formation events occurring simultaneously in the Yangtze River Delta and northeast rural sites in China - Shuo Liu; Peng Wang; Qianli Ma; Xiaojing Shen; Hanqing Kang; Junying Sun; Quan Liu; Yangmei Zhang; Muzhen Shi; Dajiang Yu; Junting Zhong; Xinyao Hu; et al. (Atmospheric Environment, 2024)

Gender disparities in summer outdoor heat risk across China: Findings from a national county-level assessment during 1991–2020 - Peng Zeng; Dachuan Shi; Marco Helbich; Fengyun Sun; Hongyu Zhao; Yaoyi Liu; Yue Che (Science of The Total Environment, 2024)

Parks may not be effective enough to improve the thermal environment in Shanghai (China) as our modified H3SFCA method suggests - Peng Zeng; Dachuan Shi; Yaoyi Liu; Tian Tian; Yue Che; Marco Helbich (Building and Environment, 2024)

The application study of the revised IMPROVE atmospheric extinction algorithm in atmospheric chemistry model focusing on improving low visibility prediction in eastern China - Chen Han; Hong Wang; Yue Peng; Zhaodong Liu; Wenjie Zhang; Yang Zhao; Huiqiong Ning; Ping Wang; Huizheng Che (Atmospheric Research, 2024)

Risk characteristics of shellfish toxins in Mytilus unguiculatus around the Zhoushan Islands, East China Sea - Guanchao Zheng; Hanyu Che; Haiyan Wu; Ling Cheng; Yuxiang Deng; Mengmeng Guo; Jixing Peng; Lijuan Liu; Zhijun Tan (Marine Pollution Bulletin, 2024)

Columnar optical-radiative properties and components of aerosols in the Arctic summer from long-term AERONET measurements - Yuanxin Liang; Huizheng Che; Xindan Zhang; Lei Li; Ke Gui; Yu Zheng; Xutao Zhang; Hengheng Zhao; Peng Zhang; Xiaoye Zhang (Science of The Total Environment, 2024)

Preparation and characteristic analysis of graphene based on coal macerals of different rank - Pengliang Ma; Yuegang Tang; Ruiqing Li; Qili Che; Peng Luo (Fuel, 2024)

Responses of radial growth to climate change for two dominant artificial coniferous trees - Jingrong Su; Shengchun Xiao; Xiaomei Peng; Cunwei Che; Peng Zhao (Dendrochronologia, 2024)

The impact of aerosol-cloud interaction on mesoscale numerical weather prediction when low-cloud and haze coexist in winter over major polluted regions of China - Wenjie Zhang; Hong Wang; Xiaoye Zhang; Yue Peng; Zhaodong Liu; Junting Zhong; Siting Li; Huizheng Che (Atmospheric Environment, 2024)

Analysis of the spatiotemporal changes in global land cover from 2001 to 2020 - Qiaoqiao Jing; Jianjun He; Yarong Li; Xianyu Yang; Yue Peng; Hong Wang; Fei Yu; Jie Wu; Sunling Gong; Huizheng Che; Xiaoye Zhang (Science of The Total Environment, 2024)

Cooling wisdom of ‘water towns’: How urban river networks can shape city climate? - Dachuan Shi; Jiyun Song; Qilong Zhong; Soe W. Myint; Peng Zeng; Yue Che (Remote Sensing of Environment, 2024)

Spatial variability of surface sediments in the Malacca strait and its implications for sedimentary environments - Lina Ai; Shengfa Liu; Shuai Cong; Hui Zhang; Peng Cao; Kaikai Wu; Wenxing Ye; Che Abd Rahim Mohamed; Xuefa Shi (Journal of Asian Earth Sciences, 2024)

Uptake, transport and accumulation of micro- and nano-plastics in terrestrial plants and health risk associated with their transfer to food chain - A mini review - Yongqiang Liu; Yue Ben; Ruijie Che; Chunqing Peng; Jining Li; Fenghe Wang (Science of The Total Environment, 2023)

Quantitative proteomics reveals the neurotoxicity of trimethyltin chloride on mitochondria in the hippocampus of mice - Zhenzhong Liu; Li Wang; Yue Wang; Siya Wu; Caiting Peng; Yu Wang; Ming Huang; Li Che; Rongjing Sun; Xi Zhao; Zuo Du; Wenhu Liu (NeuroToxicology, 2023)

Transcriptomic and metabonomic to evaluate the effect mechanisms of the growth and aroma-producing of Pichia anomala under ethanol stress - Yanru Chen; Yin Wan; Wenqin Cai; Xiaming Che; Xuehui Sun; Hong Peng; Huibo Luo; Dan Huang; Guiming Fu (Food Bioscience, 2023)

Relationship between night shift and sleep problems, risk of metabolic abnormalities of nurses: a 2 years follow-up retrospective analysis in the National Nurse Health Study (NNHS) - Heli Zhang; Jingpin Wang; Siwei Zhang; Sumei Tong; Jinping Hu; Ying Che; Lin Zhuo; Peng Wang; Rongmei Geng; Yujie Zhou; Panfeng Wang; Siyan Zhan; et al. (International Archives of Occupational and Environmental Health, 2023)
Background and purpose Efforts to improve nurses’ physical and mental health are critical to ensuring the safety and quality of the healthcare system. Long-term studies targeting the relevancy of nurses’ occupation characteristics with health conditions remain insufficient. This study aimed to examine the relationship between nurses’ night shift and sleep problems and metabolic abnormalities risk. Methods This study was a part of the National Nurse Health Study, an ambispective cohort study in China, in 2021. Based on an integration physical examination data system, this study carried out a retrospective analysis of 730 nurses from 2018 to 2020 and combined with a questionnaire survey in 2021. The STROBE guidelines were adopted for reporting. Results In the 23 (23.0, 24.0) months follow-up, higher night shift load was associated with more sleep problems such as shortened sleep duration, sleep disorders, poor sleep quality, and sleep deprivation. Moreover, night shift load was associated with chronic diseases risk factors, increasing body mass index and body fat, with more night shift density, increasing the occurrence of low levels of high-density lipoprotein cholesterol, high triglyceride, triglyceride/high-density lipoprotein cholesterol ratio, and serum uric acid. Conclusion The night shift load has become an occupational health concern, contributing to chronic diseases relevant metabolic risk factors and negative influence on sleep health. Focus on the strategies to improve the sleep quality of nurses undergoing night shift work, optimize work scheduling and ongoing monitor the relevant risk factors are essential to enhance the stability and well-being of the nursing workforce. Clinical Trials registration information: NCT04572347, on October 1, 2020. https://www.clinicaltrials.gov/ct2/show/NCT04572347

Electron activated dissociation - a complementary fragmentation technique to collision-induced dissociation for metabolite identification of synthetic cathinone positional isomers - Peng Che; J. Tyler Davidson; Jeroen Kool; Isabelle Kohler (Analytica Chimica Acta, 2023)

The microbial mechanisms by which long-term heavy metal contamination affects soil organic carbon levels - Zhineng Xiao; Changqun Duan; Shiyu Li; Ji Chen; Changhui Peng; Rongxiao Che; Chang'e Liu; Yin Huang; Runran Mei; Liangliang Xu; Pengfei Luo; Yadong Yu (Chemosphere, 2023)

Strong bacterial stochasticity and fast fungal turnover in Taihu Lake sediments, China - Shu-Hang Wang; Sheng-Wu Yuan; Fei-Fei Che; Xin Wan; Yi-Fei Wang; Dian-Hai Yang; Hai-Jiang Yang; Dong Zhu; Peng Chen (Environmental Research, 2023)

Dendrobium officinale polysaccharides improved reproductive oxidative stress injury in male mice treated with cyclophosphamide - Yi Mu; Bangwei Che; Kaifa Tang; Wenjun Zhang; Shenghan Xu; Wei Li; Jun He; Miao Liu; Peng Chen; Siwen Zhong; Guangyu Li (Environmental Science and Pollution Research, 2023)

Mixed of arbor-shrub significantly enhanced the drought stress adaptive capacity of plantation forests—An interpretation based on dendroecology - Cunwei Che; Shengchun Xiao; Xiaomei Peng; Jingrong Su; Aijun Ding (Journal of Hydrology, 2023)

Combined effect of surface PM2.5 assimilation and aerosol-radiation interaction on winter severe haze prediction in central and eastern China - Yue Peng; Hong Wang; Xiaoye Zhang; Ping Wang; Siting Li; Zhaodong Liu; Wenjie Zhang; Huizheng Che (Atmospheric Pollution Research, 2023)

The combined effects of heterogeneous chemistry and aerosol-radiation interaction on severe haze simulation by atmospheric chemistry model in Middle-Eastern China - Zhaodong Liu; Hong Wang; Yue Peng; Wenjie Zhang; Huizheng Che; Yangmei Zhang; Hongli Liu; Yaqiang Wang; Mengchu Zhao; Xiaoye Zhang (Atmospheric Environment, 2023)

How to accurately assess cultural ecosystem services by spatial value transfer? An answer based on the analysis of urban parks - Tian Tian; Qianqian Dong; Peng Zeng; Yaoyi Liu; Tao Yu; Yue Che (Urban Forestry & Urban Greening, 2023)

Greenhouse gas emissions from wastewater treatment plants in China: Historical emissions and future mitigation potentials - Mengjie Yang; Man Peng; Dong Wu; Haoyuan Feng; Yixian Wang; Yongpeng Lv; Fengyun Sun; Sanjib Sharma; Yue Che; Kai Yang (Resources, Conservation and Recycling, 2023)

Projecting multi-attribute flood regime changes for the Yangtze River basin - Chen Zhang; Fengyun Sun; Sanjib Sharma; Peng Zeng; Alfonso Mejia; Yongpeng Lyu; Jun Gao; Rui Zhou; Yue Che (Journal of Hydrology, 2023)

Report on the 3rd Board Meeting of the International Human Phenome Consortium - Mei Tian; Han Liu; Shunling Chen; Zhong Yang; Weishuo Tao; Shiwen Peng; Huiting Che; Li Jin (Phenomics, 2023)

Transcriptomic profile of symbiotic accessory nidamental gland during female maturation in bigfin reef squid - Peng-Wei Tseng; Hau-Wen Li; Chih Chen; Yung-Che Tseng; Ching-Fong Chang; Guan-Chung Wu (Frontiers in Marine Science, 2023)
The bigfin reef squid, Sepioteuthis lessoniana , are a valuable commercial species in East Asian regions such as Taiwan and Japan. A lack of genomic information limits the application of potential aquaculture techniques, especially in breeding when considering the hatching rate of offspring. In some squids and cuttlefishes, symbiotic bacteria are transmitted from the accessory nidamental gland (ANG) to the jelly coat of eggs. In Hawaiian bobtail squid, these parent-delivered mutualistic bacteria play an important role in preventing lethal biofouling of the eggs and accelerating the hatch rate of offspring. The bacterial consortium, which is housed in the female squids ANG, are governed by host selection during female maturation. Immune functions are typically used to explain the regulatory mechanism of symbioses by host selection. In this study, we evaluated the transcripts featured in bacterial selection and maintenance during ANG development using RNA-seq. Different developmental stages of ANGs (stages 1–4) were sequenced. The de novo transcriptome assembly resulted in 524,918 unigenes. Two groups, non-pigmentation group (stage 1 and stage 3) and pigmentation group (stage 4), were clustered by transcriptome-wide expression profile analysis. The gene expression analyses indicated that 9,475 differential expression genes (DEGs) in three different phases and 1,363 (14.3%) DEGs were matched in the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases. Furthermore, KEGG-enriched analysis results suggested that immune responses are a dominant pathway in the non-pigmentation group (stage 1 and stage 3) whereas lipid metabolism and metabolism of flora fermentation are dominant in the pigmentation group (stage 4). Although the host immunity plays an important role during bacterial colonization of the ANG in bigfin reef squid, our results showed that most immune-related genes had a reduced transcriptomic level in the pigmentation group compared with the non-pigmentation group. Therefore, our results provide new insight to understand the regulatory mechanisms of initial bacterial colonization and later bacterial pigmentation in the bigfin reef squid.

Changes in aerosol loading before, during and after the COVID-19 pandemic outbreak in China: Effects of anthropogenic and natural aerosol - Yuanxin Liang; Ke Gui; Huizheng Che; Lei Li; Yu Zheng; Xutao Zhang; Xindan Zhang; Peng Zhang; Xiaoye Zhang (Science of The Total Environment, 2023)

Radial growth of Korshinsk peashrub and its response to drought in different sub-arid climate regions of northwest China - Cunwei Che; Shengchun Xiao; Xiaomei Peng; Aijun Ding; Jingrong Su (Journal of Environmental Management, 2023)

Environmental, economic, and energy analysis of municipal solid waste incineration under anoxic environment in Tibet Plateau - Zeng Dan; Yuechi Che; Xutong Wang; Peng Zhou; Zhiyong Han; Duo Bu; Xuebin Lu; Wenchao Ma; Guanyi Chen (Environmental Research, 2023)

Integrated slip valve-assisted fluidic chip coupling with CRISPR/Cas12a system for nucleic acid analysis - Siwenjie Qian; Yanju Chen; Cheng Peng; Xiaofu Wang; Yang Che; Tingzhang Wang; Jian Wu; Junfeng Xu (Analytica Chimica Acta, 2023)

Brain structural connectivity sub typing in unilateral temporal lobe epilepsy - Zhensheng Li; Che Jiang; Wei Xiang; Zijuan Qi; Quwen Gao; Kairun Peng; Jian Lin; Wei Wang; Weimin Wang; Bingmei Deng (Brain Imaging and Behavior, 2022)

Total, bioavailable and free 25-hydroxyvitamin D are associated with the prognosis of patients with non-small cell lung cancer - Si-Min Peng; Na Yu; Jun Che; Jia-Ying Xu; Guo-Chong Chen; Da-Peng Li; Yu-Song Zhang; Li-Qiang Qin (Cancer Causes & Control, 2022)

Linear polyketides produced by co-culture of Penicillium crustosum and Penicillium fellutanum - Guihong Yu; Peng Sun; Reyilamu Aierken; Chunxiao Sun; Zhenzhen Zhang; Qian Che; Guojian Zhang; Tianjiao Zhu; Qianqun Gu; Mingyu Li; Dehai Li (Marine Life Science & Technology, 2022)

Characterization of municipal solid waste incineration and flue gas emission under anoxic environment in Tibet Plateau - Zeng Dan; Wenwu Zhou; Peng Zhou; Yuechi Che; Zhiyong Han; A Qiong; Bu Duo; Xuebin Lv; Qiongda Zhuoma; Jing Wang; Wang Yang; Guanyi Chen (Environmental Science and Pollution Research, 2022)

Linking hydraulic geometry, land use, and stream water quality in the Taihu Basin, China - Yaoyi Liu; Hongju Zhang; Peng Zeng; Yukun Wang; Gen Li; Fengyun Sun; Yue Che (Environmental Monitoring and Assessment, 2021)

High-order conservative and oscillation-suppressing transport on irregular hexagonal grids - Han Jiao; Xindong Peng; Yuzhang Che; Jun Chang (Meteorology and Atmospheric Physics, 2021)

Single-nucleotide polymorphisms responsible for pseudo-albinism and hypermelanosis in Japanese flounder (Paralichthys olivaceus) and reveal two genes related to malpigmentation - Bo Zhang; Kangkang Peng; Jinyuan Che; Na Zhao; Lei Jia; Dongkang Zhao; YaJuan Huang; YongGuan Liao; Xiaoxu He; Xiaoling Gong; Baolong Bao (Fish Physiology and Biochemistry, 2021)

Reclassification of Brevibacterium frigoritolerans DSM 8801T as Bacillus frigoritolerans comb. nov. Based on Genome Analysis - Guo-Hong Liu; Bo Liu; Jie-Ping Wang; Jian-Mei Che; Peng-Fei Li (Current Microbiology, 2020)

Fourth-Order Conservative Transport on Overset Grids Using Multi-Moment Constrained Finite Volume Scheme for Oceanic Modeling - Juan Gu; Xindong Peng; Yongjiu Dai; Yuzhang Che (Journal of Ocean University of China, 2020)

The Effect of Abnormal Iron Metabolism on Osteoporosis - Jingmin Che; Jiancheng Yang; Bin Zhao; Ge Zhang; Luyao Wang; Songlin Peng; Peng Shang (Biological Trace Element Research, 2020)

Comparative Analysis of Nutrient Composition of Caulerpa lentillifera from Different Regions - Meijian Zhang; Yurong Ma; Xinyi Che; Zumei Huang; Peng Chen; Guanghua Xia; Meihui Zhao (Journal of Ocean University of China, 2020)

Seminal Plasma Exosomes: Promising Biomarkers for Identification of Male and Pseudo-Males in Cynoglossus semilaevis - Bo Zhang; Na Zhao; Lei Jia; Kang Peng; Jinyuan Che; Kunming Li; Xiaoxu He; Jinsheng Sun; Baolong Bao (Marine Biotechnology, 2019)

Prototype Deep Brain Stimulation System with Closed-Loop Control Feedback for Modulating Bladder Functions in Traumatic Brain Injured Animals - En Jen; Chii-Wann Lin; Tsung-Hsun Hsieh; Yi-Chun Chiu; Tsung-Che Lu; Shih-Ching Chen; Meng-Chao Chen; Chih-Wei Peng (Journal of Medical and Biological Engineering, 2018)

Applying the WRF Double-Moment Six-Class Microphysics Scheme in the GRAPES_Meso Model: A Case Study - Meng Zhang; Hong Wang; Xiaoye Zhang; Yue Peng; Huizheng Che (Journal of Meteorological Research, 2018)

Comparison of Submicron Particles at a Rural and an Urban Site in the North China Plain during the December 2016 Heavy Pollution Episodes - Xiaojing Shen; Junying Sun; Xiaoye Zhang; Yangmei Zhang; Yaqiang Wang; Kaiyan Tan; Peng Wang; Lu Zhang; Xuefei Qi; Haochi Che; Zhouxiang Zhang; Junting Zhong; et al. (Journal of Meteorological Research, 2018)

Suppressive effect of microRNA319 expression on rice plant height - Wei-Ting Liu; Peng-Wen Chen; Li-Chi Chen; Chia-Chun Yang; Shu-Yun Chen; GuanFu Huang; Tzu Che Lin; Hsin-Mei Ku; Jeremy J. W. Chen (Theoretical and Applied Genetics, 2017)

In-flight Excavation of a Loess Slope in a Centrifuge Model Test - Zhongjie Fan; P. H. S. W. Kulatilake; Jianbing Peng; Wenyue Che; Yazhe Li; Zhenjiang Meng (Geotechnical and Geological Engineering, 2016)

Complex longitudinal diversification across South China and Vietnam in Stejneger's pit viper, Viridovipera stejnegeri (Schmidt, 1925) (Reptilia: Serpentes: Viperidae) - Peng Guo; Qin Liu; Fei Zhu; Guang H. Zhong; Xin Chen; Edward A. Myers; Jing Che; Liang Zhang; Thomas Ziegler; Truong Q. Nguyen; Frank T. Burbrink (Molecular Ecology, 2016)
Viridovipera stejnegeri is one of the most common pit vipers in Asia, with a wide distribution in southern China and Vietnam. We investigated historical demography and explored how the environment and climatic factors have shaped genetic diversity and the evolutionary history of this venomous snake. A total of 171 samples from 47 localities were sequenced and analysed for two mitochondrial gene fragments and three nuclear genes. Gene trees reveal the existence of two well‐supported clades (Southwest China and Southeast China) with seven distinct and strongly supported, geographically structured subclades within V. stejnegeri . Estimation of divergence time and ancestral area suggests that V. stejnegeri originated at ~6.0 Ma in the late Miocene on the Yunnan–Guizhou Plateau. The estimated date of origin and divergence of the island populations of Taiwan and Hainan closely matches the geological origin of the both islands. The mt DNA gene tree reveals the presence of west–east diversification in V. stejnegeri populations. Complex orogenesis and heterogeneous habitats, as well as climate‐mediated habitat differentiation including glacial cycles, all have influenced population structure and the distribution of this taxon. The validity of V. stejnegeri chenbihuii is questionable, and this subspecies most probably represents an invalid taxon.

Molecular phylogeography of white‐lipped tree viper ( Trimeresurus ; Viperidae) - Fei Zhu; Qin Liu; Jing Che; Liang Zhang; Xin Chen; Fang Yan; Robert Murphy; Cong Guo; Peng Guo (Zoologica Scripta, 2016)
The white‐lipped tree viper ( Trimeresurus albolabris ) is one of the most common venomous snakes with medicine importance in South East Asia. To explore the genetic diversity, population structure and evolutionary history of Trimeresurus albolabris, we collected 98 samples from 27 localities covering its entire distribution. Two mitochondrial gene fragments (cyt‐b and ND‐4) and two nuclear genes (RAG‐1 and NT‐3) were sequenced and analysed. Bayesian inference and maximum‐likelihood methods were employed to reconstruct the phylogenetic relationships among populations based on the two mitochondrial fragments, and the median‐joining networks were depicted using nuclear genes. Divergence date and ancestral area were estimated, and the population demographic history was inferred. Both phylogenetic analyses consistently uncovered that Trimeresurus albolabris was monophyletics, with five geographically structured lineages. Divergence date and ancestral area estimation indicated that T. albolabris originated in northern Thailand and eastern Myanmar at c . 7.15 Ma. Population dynamics analyses showed the southern China lineage has experienced population expansion and contraction, but the others have not. Both the interglacial expansion and the highly heterogeneous habitats resulting from the uplift of the Plateau played a joint role in shaping the present distribution and population structure. The evolutionary history of T. albolabris can be explained by a pattern of two direction dispersal: first from North to South, and then from West to East.

Aspirin and nonsteroidal anti-inflammatory drugs after but not before diagnosis are associated with improved breast cancer survival: a meta-analysis - Xuan-zhang Huang; Peng Gao; Jing-xu Sun; Yong-xi Song; Cheng-che Tsai; Jing Liu; Xiao-wan Chen; Ping Chen; Hui-mian Xu; Zhen-ning Wang (Cancer Causes & Control, 2015)

Therapeutic Efficacy of Neuro AiD™ (MLC 601), a Traditional Chinese Medicine, in Experimental Traumatic Brain Injury - Ming-Che Tsai; Ching-Ping Chang; Syue-Wei Peng; Kai-Sheng Jhuang; Yi-Hsien Fang; Mao-Tsun Lin; Thomas Chang-Yao Tsao (Journal of Neuroimmune Pharmacology, 2015)

The Bifunctional Liposomes Constructed by Poly(2-ethyl-oxazoline)-cholesteryl Methyl Carbonate: an Effectual Approach to Enhance Liposomal Circulation Time, pH-Sensitivity and Endosomal Escape - Huan Xu; Wei Zhang; Yan Li; Fei F. Ye; Peng P. Yin; Xiu Yu; Mei N. Hu; Yuan S. Fu; Che Wang; De J. Shang (Pharmaceutical Research, 2014)

Urinary Perchlorate Exposure and Risk in Women of Reproductive Age in a Fireworks Production Area of China - Qin Li; Yun-jiang Yu; Fei-fei Wang; Shi-wu Chen; Yan Yin; Hai-peng Lin; Fei Che; Peng Sun; Juan Qin; Jie Liu; Hong-mei Wang (Archives of Environmental Contamination and Toxicology, 2014)

Synthesis and antibacterial evaluation of furan derivatives bearing a rhodanine moiety - Jian Che; Chang-Ji Zheng; Ming-Xia Song; Ya-Jing Bi; Yi Liu; Yin-Jing Li; Yan Wu; Liang-Peng Sun; Hu-Ri Piao (Medicinal Chemistry Research, 2014)

Statin use and risk of bladder cancer: a meta-analysis - Xiao-long Zhang; Jiang Geng; Xiao-peng Zhang; Bo Peng; Jian-ping Che; Yang Yan; Guang-chun Wang; Sheng-qiang Xia; Yan Wu; Jun-hua Zheng (Cancer Causes & Control, 2013)

Moscatilin inhibits migration and metastasis of human breast cancer MDA-MB-231 cells through inhibition of Akt and Twist signaling pathway - Hui-Chen Pai; Li-Hsun Chang; Chieh-Yu Peng; Ya-Ling Chang; Chien-Chih Chen; Chien-Chang Shen; Che-Ming Teng; Shiow-Lin Pan (Journal of Molecular Medicine, 2013)

Triterpenoid saponins from Ilex mamillata C.Y. Wu ex C.J. Tseng - Che Yan-Yun; Zhang Liang; Li Ning; Zeng Ke-Wu; Tu Peng-Fei (Natural Product Research, 2012)

Helicobacter pylori HP0876 is Dispensable for Heme–Iron Acquisition but Attenuates Bacterial Adherence to Gastric Epithelial Cells - Tao Liu; Yun Shi; Xiao-fei Liu; Ying Guo; Xu-hu Mao; Che Tan; Yuan Zhuang; Liu-sheng Peng; Jin-yu Zhang; Quan-ming Zou (Current Microbiology, 2012)

Simulation of direct radiative forcing of aerosols and their effects on East Asian climate using an interactive AGCM-aerosol coupled system - Hua Zhang; Zhili Wang; Zaizhi Wang; Qianxia Liu; Sunling Gong; Xiaoye Zhang; Zhongping Shen; Peng Lu; Xiaodong Wei; Huizheng Che; Laurent Li (Climate Dynamics, 2012)

Baicalein attenuates intimal hyperplasia after rat carotid balloon injury through arresting cell-cycle progression and inhibiting ERK, Akt, and NF-κB activity in vascular smooth-muscle cells - Chieh-Yu Peng; Shiow-Lin Pan; Ying-Wen Huang; Jih-Hwa Guh; Ya-Ling Chang; Che-Ming Teng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Differential expression of genes encoding 1-aminocyclopropane-1-carboxylate synthase in Arabidopsis during hypoxia - Hsiao-Ping Peng; Ter-Yun Lin; Ning-Ning Wang; Ming-Che Shih (Plant Molecular Biology, 2005)